2011
DOI: 10.12693/aphyspola.120.35
|View full text |Cite
|
Sign up to set email alerts
|

The Features of Real Part of Admittance in the Nanocomposites (Fe45Co45Zr10)x(Al2O3)100 - xManufactured by the Ion-Beam Sputtering Technique with Ar Ions

Abstract: The temperature and frequency dependences of the admittance real part σ(T, f ) in granular (Fe 45 Co 45 Zr 10 ) x (Al 2 O 3 ) 100−x nanocomposite films around the percolation threshold x C were investigated. The behaviour of σ(T, f ) vs. the temperature and frequency over the ranges 77-300 K and 50 Hz-1 MHz, respectively, displays the predominance of an activation (hopping) conductance mechanism for the samples below the percolation threshold x C and of a metallic one beyond the x C determined as 54 ± 2 at.%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The method to manufacture the films and the characterization of their structures are described in detail elsewhere. 15,[26][27][28] The compound target contained Fe 45 Co 45 Zr 10 alloy plates with PbZrTiO 3 stripes arranged on their surfaces. The irregular distribution of the PbZrTiO 3 stripes (with continuously increasing spaces between them) on the target surfaces allows synthesis of films with variable metalto-dielectric ratios, x (depending on the mutual arrangement of the targets and substrates) in one technological cycle.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The method to manufacture the films and the characterization of their structures are described in detail elsewhere. 15,[26][27][28] The compound target contained Fe 45 Co 45 Zr 10 alloy plates with PbZrTiO 3 stripes arranged on their surfaces. The irregular distribution of the PbZrTiO 3 stripes (with continuously increasing spaces between them) on the target surfaces allows synthesis of films with variable metalto-dielectric ratios, x (depending on the mutual arrangement of the targets and substrates) in one technological cycle.…”
Section: Methodsmentioning
confidence: 99%
“…In our earlier studies on (Fe 45 Co 45 Zr 10 ) x (Al 2 O 3 ) (100Àx) nanocomposite granular films, 8,[13][14][15][16] it was shown that deposition conditions play the key role in the phase composition of the films. In particular, transmission electron microscopy, x-ray diffraction (XRD) analysis, and Mössbauer spectroscopy (MS) measurements revealed that adding oxygen to the sputtering atmosphere results in formation of CoFe-based oxide shells around the FeCoZr nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations